2017
DOI: 10.18632/oncotarget.17119
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase 1 deficiency attenuates CCl4-induced fibrosis through Th17 cells down-regulation and tryptophan 2,3-dioxygenase compensation

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1) is an intracellular rate-limiting enzyme in the metabolism of tryptophan along the kynurenine pathway, subsequently mediating the immune response; however, the role of IDO1 in liver fibrosis and cirrhosis is still unclear. In this study, we investigated the role of IDO1 in the development of hepatic fibrosis and cirrhosis. Patients with hepatitis B virus-induced cirrhosis and healthy volunteers were enrolled. For animals, carbon tetrachloride (CCl4) was used to establish li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Our data revealed that pretreatment with APE could normalize the levels of these parameters. Some reports have shown that CCl 4 administration led to collagen deposition, destruction of cellular boundaries, central vein congestion and inflammation of liver tissue [11,25,26]. In this study, the histopathological examination of the liver indicated that CCl 4 intoxication caused disruption of cellular and lobular structures, inflammation and necrosis.…”
Section: Discussionsupporting
confidence: 52%
“…Our data revealed that pretreatment with APE could normalize the levels of these parameters. Some reports have shown that CCl 4 administration led to collagen deposition, destruction of cellular boundaries, central vein congestion and inflammation of liver tissue [11,25,26]. In this study, the histopathological examination of the liver indicated that CCl 4 intoxication caused disruption of cellular and lobular structures, inflammation and necrosis.…”
Section: Discussionsupporting
confidence: 52%
“…Among these processes, FZHY formula had been reported to cure liver fibrosis by positive regulation of macromolecule metabolic process ( Gao et al, 2016 ) and positive regulation of macromolecule biosynthetic process ( Liu et al, 2006 ; Cheng et al, 2013 ). In addition, cellular responses to endogenous stimulus ( Huang et al, 2016 ) and regulation of cell death ( Zhong et al, 2017 ) have been reported to be closely related to liver fibrosis, further experiments are needed to validate the interaction between FZHY formula and these two biological processes.…”
Section: Resultsmentioning
confidence: 99%
“…Greater tryptophan metabolism during NMP is further significant as the liver oversees 90% of TRP catabolism via the KP, which generates both pro- and anti-inflammatory signaling metabolites [ 36 , 37 ]. Two rate-limiting enzymes catalyze the conversion of TRP to N-formylkynurenine in the first step of the KP: tryptophan 2, 3-dioxygenase (TDO) and indolamine-2,3-dioxygenase (IDO).…”
Section: Discussionmentioning
confidence: 99%